Live‐Cell Glycocalyx Engineering. (21st February 2023) - Li, Yuxin; Wang, Mingzhen; Hong, Senlian
Abstract: A heavy layer of glycans forms a brush matrix bound to the outside of all the cells in our bodies; it is referred to as the "sugar forest" or glycocalyx. Beyond the increased appreciation of the glycocalyx over the past two decades, recent advances in engineering the glycocalyx on live cells have spurred the creation of cellular drugs and novel medical treatments. The development of new tools and techniques has empowered scientists to manipulate the structures and functions of cell‐surface glycans on target cells and endow target cells with desired properties. Herein, we provide an overview of live‐cell glycocalyx engineering strategies for controlling the cell‐surface molecular repertory to suit therapeutic applications, even though the realm of this field remains young and largely unexplored. Abstract : New advances in developing tools to engineer surface glycocalyx on live cells and donor organs have paved a transformative road towards glycotherapy for anticancer, anti‐inflammation, and anti‐autoimmune agents, as well as transplantation and other uses.